Online Games and Mental Health of Generation Z: A Case Study on Male Adolescents at SMK MAN 5 Tasikmalaya - Azahra, Astrid Sulistya; Kalfin, Kalfin; Hidayana, Rizki Apriva (International Journal of Ethno-Sciences and Education Research, 2024)
This research investigates the impact of online games on the mental health of Generation Z, with a focus on male adolescents at SMK MAN 5 Tasikmalaya. Quantitative research methods were used to collect data through questionnaires regarding the duration of playing online games and observations of mental health. The results of data analysis show that there is a significant relationship between the duration of playing online games and mental health in male adolescents. It was found that online gaming addiction can result in decreased mental health, including social isolation, decreased academic performance, and emotional disorders. Therefore, efforts need to be made to manage the use of online games wisely to minimize the negative impact on Generation Z's mental health.